2020
DOI: 10.1155/2020/1085324
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strontium Ranelate on Fracture Healing: An Animal Study

Abstract: Background. Strontium ranelate (StR) is an antiosteoporotic agent previously utilized for the enhancement of fracture union. We investigated the effects of StR on fracture healing using a rabbit model. Methods. Forty adult female rabbits were included in the study and were divided in 2 equal groups, according to StR treatment or untreated controls. All animals were subjected to osteotomy of the ulna, while the contralateral ulna remained intact and served as a control for the biomechanical assessment of fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Strontium ranelate (SrR) is composed of two stable divalent strontium ions and one ranelate. Several animal experiments have shown that SrR can accelerate the healing process and improve bone mechanical properties 153–155 . So, adding SrR into the tissue engineering scaffold to repair bone defects and promote bone regeneration under osteoporotic conditions have become a potential topical application.…”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strontium ranelate (SrR) is composed of two stable divalent strontium ions and one ranelate. Several animal experiments have shown that SrR can accelerate the healing process and improve bone mechanical properties 153–155 . So, adding SrR into the tissue engineering scaffold to repair bone defects and promote bone regeneration under osteoporotic conditions have become a potential topical application.…”
Section: Anti‐osteoporosis Therapiesmentioning
confidence: 99%
“…Several animal experiments have shown that SrR can accelerate the healing process and improve bone mechanical properties. [153][154][155] So, adding SrR into the tissue engineering scaffold to repair bone defects and promote bone regeneration under osteoporotic conditions have become a potential topical application. Including SrR-incorporated bioceramic scaffolds, 156 composite gelatin coatings containing SrR-carrying halloysite nanotubes.…”
Section: Strontium Saltmentioning
confidence: 99%
“…The results of the meta-analysis demonstrated that the administration of Sr ranelate (SrRa) is associated with a 31% and 40% decrease in osteoporotic fractures and vertebral fractures in postmenopausal osteoporosis cases, respectively [ 267 ]. Sr ranelate was also shown to promote bone fracture healing [ 268 ]. However, SrRa did not improve wrist fracture healing in advanced-age Italians suffering from wrist fracture, while being administered during the acute phase [ 269 ].…”
Section: Strontium (Sr)mentioning
confidence: 99%
“…The unique dual action of SRR on bone metabolism is attributed to its ability to influence osteoblasts (bone-forming cells) and osteoclasts (bone-resorbing cells) activities [14]. This equilibrium not only enhances bone mineral density but also reduces the risk of fractures, a frequent complication of osteoporosis [15]. Transitioning to the context of intervertebral discs, the health and integrity of the adjacent vertebral bones play a significant role in determining disc health.…”
Section: Ivyspringmentioning
confidence: 99%